Influence of the specific surface area and silver crystallite size of mesoporous Ag/SrTiO3 on the selectivity enhancement of ethylene oxide production. Issue 12 (30th September 2019) - Adhami, Shekoufeh; Esfahany, Mohsen Nasr; Eränen, Kari; Peurla, Markus; Mäkilä, Ermei; Murzin, Dmitry Yu; Salmi, Tapio
ABSTRACT: Background: Ethylene oxide, which is industrially produced by ethylene epoxidation, is an important versatile chemical intermediate, thus its selectivity enhancement can bring substantial economic profits. In this work, the effects of two important, but still debatable, factors, i.e. catalyst specific surface area and active phase crystallite size, on the catalyst selectivity enhancement were investigated. Surfactant assisted sol–gel method with good control ability on the pores structure was selected to produce mesoporous strontium titanate (SrTiO3 ) nanocrystals with various specific surface area. The SrTiO3 nanocrystals were used as the supports of silver (Ag) for ethylene epoxidation. Results: The Ag/SrTiO3 catalysts with various surface areas were obtained by changing the surfactant‐alkoxide ratio and the calcination time. The ethylene oxide selectivity of the prepared catalysts was examined in a laboratory‐scale fixed bed reactor. The best performance was observed at the lowest surfactant–alkoxide ratio of 0.2 and calcination time of 4 h, with the surface area of 1.7 m 2 /g and Ag crystallite size of 15 nm. Conclusion: The best catalyst selectivity was observed at the lowest surface area and the highest average Ag crystallite size. In this condition, the selectivity of the Ag/SrTiO3 catalyst without any modifier was superior to a commercial Ag/Al2 O3 catalyst with 3.7m 2 /g surface area and alkaline earth metal modifiers. © 2019 Society of Chemical Industry